Cloning of A Gene Encoding Protease from Bacillus halodurans CM1 into Escherichia coli DH5α - Furgeva, Natasha; Helianti, Is; Ferniah, Rejeki Siti; K, Hermin Pancasakti (Berkala Bioteknologi, 2021)
Bacillus halodurans strain CM1 was an Indonesia alkalothermophilic bacteria isolated from Cimanggu Hot Spring, Bandung, West Java. The activity of alkalo thermophilic protease enzyme from B. halodurans CM1 was detected. Nowadays, alkalothermophilic protease enzyme was applied for the eco-friendly industrial purpose, for example, as additive substance in detergent product. For the production and application of protease in the future, the cloning of protease gene from B. halodurans CM1 into E. coli was conducted. The protease gene was isolated from B. halodurans by PCR approach using primers designed based on the GenBank database. The PCR product then ligated into pGEM-T Easy vector, transformed into Escherichia coli DH5α, verified, and analyzed using DNA sequencing and bioinformatic tools BLAST. The results showed that 1086 bp protease gene was obtained and had 99% similarity with that of alkalostable protease from B. halodurans C-125. When the culture of this positive recombinant E. coli DH5α containing the protease gene spotted onto calcium caseinate agar, the clear zone appeared after incubation at 50 °C. It showed that the protease gene was expressed in this recombinant E.coli DH5α.